Visualizing the internal structure of the charge-density-wave state in CeSbTe - Xinglu Que; Qingyu He; Lihui Zhou; Shiming Lei; Leslie Schoop; Dennis Huang; Hidenori Takagi (Nature Communications)
Abstract The collective reorganization of electrons into a charge density wave has long served as a textbook example of an ordered phase in condensed matter physics. Two-dimensional square lattices with p electrons are well-suited to the realization of charge density waves, due to the anisotropy of the p orbitals and the resulting one dimensionality of the electronic structure. In spite of a long history of study of charge density waves in square-lattice systems, few reports have recognized the significance of a hidden orbital degree of freedom. The degeneracy of p x and p y electrons may give rise to orbital patterns in real space that endow the charge density wave with additional broken symmetries or unusual order parameters. Here, we use scanning tunneling microscopy to visualize the internal structure of the charge-density-wave state of CeSbTe, which contains Sb square lattices with 5p electrons. We image atomic-sized, anisotropic lobes of charge density with periodically modulating anisotropy, which we interpret in terms of a superposition of p x and p y bond density waves. Our results support the fact that delocalized p orbitals can reorganize into emergent electronic states of matter.